The Association Between Financial Incentives and Job Performance Among Primary Care Providers in Six Provinces of China - Wang H; Zhao S; Liu Q; Wang J; Yuan B (Dove Medical Press, 2022)
Haipeng Wang,1,2,* Shichao Zhao,3,* Qian Liu,4 Jinyu Wang,3 Beibei Yuan5 1Centre for Health Management and Policy Research, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2NHC Key Laboratory of Health Economics and Policy Research, Shandong University, Jinan, People's Republic of China; 3School of Public Administration, Shandong Normal University, Jinan, People's Republic of China; 4School of Social Development and Public Policy, Beijing Normal University, Beijing, People's Republic of China; 5China Center for Health Development Studies, Peking University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Beibei Yuan, China Center for Health Development Studies, Peking University, Box 505, 38 Xue Yuan Road, Haidian District, Beijing, 100191, People's Republic of China, Email beibeiyuan@bjmu.edu.cnObjective: This study aims to explore the association between financial incentives and job performance of primary care providers (PCPs) from a nationally representative survey in China.Methods: This is a cross-sectional study conducted in six provinces of China in 2019. A sample of 1388 PCPs participated in the survey was selected using a stratified cluster sampling method. A self-administered questionnaire composed of socio-demographic, work-related characteristics, financial incentives received by PCPs and their job performance was used. The association between financial incentives and job performance are analyzed using logistic regression model. The significance level for statistics is set at P < 0.05.Results: The PCPs with higher real income level have lower contextual performance (OR = 0.67, p < 0.01) and learning performance (OR = 0.63, p < 0.01) than those with lower real income level. The PCPs with the expectation of income rising above 50% have lower contextual performance (OR = 0.66, p < 0.05) than those with the expectation of income rising above 20%. The PCPs with preference for monetary income have lower task performance (OR = 0.62, p < 0.01), contextual performance (OR = 0.55, p < 0.01) and learning performance (OR = 0.57, p < 0.01) than those without lower preference for monetary income. The percent of performance-based income has no significant effect on all the three dimensions of job performance.Conclusion: Financial incentive was regarded as the most important motivating factor of PCPs in China, but existing financial incentives received by PCPs could not improve their job performance. The findings can be attributed to the unsatisfying total income level, "intrinsic motivation crowding out" effect, and the poorly designed performance-based salary system for PCPs. Policy attention is called for to continuing efforts and system reform to increase the total income level for PCPs in China, and improve the performance-based salary system to better motivate PCPs and improve their job performance.Keywords: financial incentive, job performance, primary care providers, China